Exploring the grand challenges for next generation E-business 8th Workshop on E-Business, WEB 2009, Phoenix, AZ, USA, December 15, 2009, Revised Selected Papers - Workshop on E-Business 2009 Phoenix, Ariz.); Sharman, Raj.; Rao, H. Raghav; Raghu, T. S.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book is based on a selection of thoroughly revised and extended best papers from the 8th Workshop on E-Business (WEB 2009) held in Phoenix, AZ, USA, on December 15th, 2009. The 29 papers, which were selected from 70 presentations at the workshop, highlight the enormous developments and potential of e-business at a time when new technologies like cloud computing, collective intelligence, and multi-sided platforms are burgeoning. Among the topics covered are Web-based information systems, RFID and supply chain management, process modeling and standardization, security and privacy issues, social networking and mobility, e-services and market mechanisms, IT portfolio management, and other special topics in e-business such as electronic invoicing.
Electronic reproduction.
Keywords: Electronic commerce -- Congresses; Electronic books